VALPROIC ACID TOXICITY INDUCED BY LACOSAMIDE: A RARE CASE REPORT - Kumar, Karthika Ashok; Chandran, Chanshi; Reghu, Remya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Valproic acid is commonly used in the treatment of both focal and generalized epilepsies and is often tolerated well.Valproic acid is usually tolerated well, but serious complications, including hepatotoxicity and hyperammonemic encephalopathy, may occur. Here we report a case of valproic acid induced hyperammonemic encephalopathy on concomitant use with lacosamide. Â